2004
DOI: 10.1136/ard.2002.001594
|View full text |Cite
|
Sign up to set email alerts
|

Long term prognosis of children born to lupus patients

Abstract: Objective: To determine the long term prognosis of children of patients with systemic lupus erythematosus (SLE). Methods: Children of patients with SLE were invited to attend our clinic for physical examination and laboratory tests. A total of 195 children (aged 4 months to 26 years; male = 82, female = 113) were examined in 1991, 1995, 1997, and 1998. Results: Two cases were diagnosed as SLE at the first visit and were excluded from the second visit. A significantly higher percentage (52/195 (27%)) of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
0
10
0
3
Order By: Relevance
“…These were mainly shown by studies on identical twins 6 in addition to observing a higher disease frequency in the relatives of patients with SLE 7 and children of mothers with SLE. 8 Extensive studies have linked SLE susceptibility to genes of the human leukocyte antigen (HLA) region. However, the extent of this association varies among different population.…”
mentioning
confidence: 99%
“…These were mainly shown by studies on identical twins 6 in addition to observing a higher disease frequency in the relatives of patients with SLE 7 and children of mothers with SLE. 8 Extensive studies have linked SLE susceptibility to genes of the human leukocyte antigen (HLA) region. However, the extent of this association varies among different population.…”
mentioning
confidence: 99%
“…Studies including monozygotic twins and familial aggregation support the idea of genetic predisposition. The risk of developing SLE among siblings have been shown to be almost 30-fold higher than in the general population and ANA-positivity has been shown to be present in 27% of offspring to mothers with SLE compared to 7% in controls (22,23). However, in families with several affected members, the genetic component is complex and does not follow a classical Mendelian inheritance pattern, and only a few cases can be attributed to highly penetrating rare mutations (24).…”
Section: Pathogenesis and Aetiologymentioning
confidence: 99%
“…Moreover, future mothers might be worried that their children may be affected by SLE, even if this risk is small. There is evidence that SLE occurrence is increased in the offspring of patients with SLE, and prevalence has been estimated at ∼4% in the children of parents with SLE (29). Other studies have shown that up to 12% of SLE patients had first‐degree relatives with SLE or other connective tissue diseases (30).…”
Section: Childbearing Decisionmentioning
confidence: 99%
“…This overestimated the number of pregnancies per woman with a diagnosis of SLE, because those who did not achieve any pregnancy were excluded. In this study, a total of 79 women with SLE and 80 healthy subjects with a mean (range) age of 33.1 (17–62) years were evaluated. There were a total of 183 pregnancies among 53 patients before the clinical diagnosis of SLE, which resulted in 42 spontaneous abortions and 141 live births.…”
Section: Fertilitymentioning
confidence: 99%